Is screening and intervention for microalbuminuria worthwhile in patients with insulin dependent diabetes?. Issue 6894 (26th June 1993) - Borch-Johnsen, K; Wenzel, H; Viberti, G C; Mogensen, C E
Abstract : OBJECTIVE–To analyse the cost-benefit of screening for and antihypertensive treatment of early renal disease indicated by microalbuminuria in patients with insulin dependent diabetes mellitus. DESIGN–Previously published data were used to estimate transition probabilities for each step from normoalbuminuria until death. The effect of intervention on urinary albumin excretion rate by antihypertensive treatment was arbitrarily set at three different levels. All direct costs (screening, antihypertensive treatment, treatment of end stage renal failure) were included in the cost-benefit analysis by using real discount rates of 2.5% and 6%. SETTING–Computer simulation. SUBJECTS–Simulated cohort of 8000 patients. MAIN OUTCOME MEASURES–Mortality, incidence of diabetic nephropathy, incidence of end stage renal failure, and costs versus savings. RESULTS–Assuming treatment effects of 33% and 67% median life expectancy increased by four to 14 years, respectively, and the need for dialysis or transplantation decreased by 21% to 63%. Costs and savings would balance if the annual rate of increase of albuminuria was decreased from 20% to 18% a year. CONCLUSIONS–Screening and intervention programmes are likely to have life saving effects and lead to considerable economic savings.